INFLUENCE OF ONLINE GROCERY SHOPPING BEHAVIOR AMONG WORKING WOMEN: A STUDY FOCUSED ON TIRUVALLUR DISTRICT - K. Shakila; Golden.S, Anthony Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the online grocery buying behavior of working women, focusing on key factors that influence their purchasing decisions, including convenience, product variety, trust, and time efficiency. As online grocery shopping gains traction, understanding these drivers is essential for e-commerce platforms aiming to capture this busy demographic. A survey was conducted with 295 working women in Tiruvallur District, and Structural Equation Modeling (SEM) was used to analyze the relationships between these factors and online buying behavior. The results indicate that convenience and time efficiency significantly impact online grocery shopping preferences, as they cater to the time constraints faced by working women. Additionally, a wide product variety and trust in online platforms are crucial for encouraging purchases and repeat transactions. The findings suggest that online grocery retailers can better engage working women by enhancing convenience features, offering diverse product options, building trust, and promoting time-saving tools, ultimately fostering customer loyalty and growth in this market segment.